The water-agro-food system: upscaling from the Seine river basin to the global scale - Billen, Gilles; Garnier, Josette (Comptes Rendus. Géoscience)
Starting from the study of the major impacts of human activity in the Seine river basin on ground- and surface water quality, due to domestic and industrial wastewater and to intensive agricultural practices, a research framework was developed, combining the analysis of the agricultural systems, their connection to food requirement by local population and trade exchanges with other regions or countries, as well as the losses to the hydrosphere and atmosphere in terms of nitrogen, phosphorus, silica and carbon, and their associated environmental problems. From the Seine basin regional scale, the concept of water agro-food system was enlarged to the national, European and global scales. Coupling the GRAFS approach (Generalized Representation of Agro-Food Systems) to the Riverstrahler model (a biogeochemical drainage network model), allowed to make the link between the different issues of food production, river water quality and nutrient delivery to the coastal zone, as well as to develop an indicator of the risk for coastal water eutrophication (ICEP) now being included as an indicator for the United Nation Sustainable Development Goal (SDG) 14.